Beam Dynamic Equations for Predictive Modeling of Semicircular Canal Pathologies - Gourinat, Yves; Guillaumont, Marie-Stéphane (Annals of Mathematics and Physics, 2024)
This short paper presents a general strategy devoted to an original analytical approach of looped 1.5D equations. It considers particular properties of rod/beam equations for wave and structural modal representation. Specific boundary conditions introduce local singularities representing discontinuities and inversions. The process presented in the paper links this kind of original analysis with possible models of the physiological and pathological dynamic behavior of solid-fluid interaction in inner-ear elements such as the anterior and superior semicircular canals. Thus, these models propose a robust representation of these elements, offering observation/control perspectives for diagnostics and cure.